2005
DOI: 10.4049/jimmunol.175.8.5240
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Resistance/Susceptibility in T Cells of Nonobese Diabetic Mice Conferred by MHC and MHC-Linked Genes

Abstract: Polymorphism of MHC and MHC-linked genes is tightly associated with susceptibility to type 1 diabetes (T1D) in human and animal models. Despite the extensive studies, however, the role of MHC and MHC-linked genes expressed by T cells on T1D susceptibility remains unclear. Because T cells develop from TCR− thymic precursor (pre-T) cells that undergo MHC restriction mediated by thymic stroma cells, we reconstituted the T cell compartment of NOD.scid-RIP-B7.1 mice using pre-T cells isolated from NOD, NOR, AKR, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Because the positive selection for iNKT cells takes place among double positive thymocytes, a deficient positive selection in NOD mice is likely intrinsic for the T lineage. Therefore, the result of present study is consistent with early studies in which we and others found that development of iNKT cells in the NOD.scid reconstituted with pre-T cells depended on the donor origin (31,36,37). The positive selection of iNKT cells depends on endogenous lipid Ags displayed by CD1d molecules, and also requires homotypic interactions of Slam receptors and downstream recruitment of the adaptor SLAM-associated protein (SAP) (2,6,38).…”
Section: Discussionsupporting
confidence: 82%
“…Because the positive selection for iNKT cells takes place among double positive thymocytes, a deficient positive selection in NOD mice is likely intrinsic for the T lineage. Therefore, the result of present study is consistent with early studies in which we and others found that development of iNKT cells in the NOD.scid reconstituted with pre-T cells depended on the donor origin (31,36,37). The positive selection of iNKT cells depends on endogenous lipid Ags displayed by CD1d molecules, and also requires homotypic interactions of Slam receptors and downstream recruitment of the adaptor SLAM-associated protein (SAP) (2,6,38).…”
Section: Discussionsupporting
confidence: 82%
“…Similar to a number of other transgenic models and T-cell lines (32,33), spontaneous progression to diabetes is enhanced by homozygosity for H-2 g7 , consistent with a major histocompatibility complex gene-dose effect in these mice (32,34). Because spontaneous diabetes occurs in unmanipulated BDC12-4.1 transgenic RAG Ϫ/Ϫ mice in spite of severe lymphopenia and a lack of CD8 and B-cells, these transgenic CD4 ϩ T-cells specific for B:9-23 are sufficient for disease in NOD mice (without in vitro activation).…”
Section: B:9-23 and Autoimmune Diabetesmentioning
confidence: 99%